Sociocultural Information Gap in the Dive Tourism Industry: Evidence from Komodo National Park - Berto, Agustinus Rusdianto; Murwani, Endah (Jurnal Ilmu Komunikasi, 2022)
Through the perspective of partnership for Sustainable Development Goals (SDGs 17th), this study aims to identify and describe the information gaps among stakeholders of the dive tourism industry of Komodo National Park as one of the super-priority tourism destinations in Indonesia. Researchers studied documents, performed field observation, and conducted in-depth interviews with 20 stakeholders. Qualitative content analysis revealed several notable findings. First, the information gaps among stakeholders are generally linked to knowledge disparity about tourism-technical and local sociocultural issues. Sociocultural information, particularly on environment preservation issues, shows the tendency to predominate everyday discourse rather than tourism technical information. Second, the foreigner community appears to be better than local stakeholders at mastering the sociocultural information discourse, particularly in terms of collaboration on environment preservation information. Further studies are needed to examine the interaction among actors predominating the sociocultural information management and their strategies to collaborate in maximizing the role of Destination Management Organization-Destination Governance (DMO-DG).